Long history, deep time : deepening histories of place - McGrath, Ann, 1956-; Jebb, Mary Anne (Aboriginal history monograph series., 2015)
"For all the methodological innovations that the discipline of academic history has seen since its birth in Europe in the late-eighteenth and early-nineteenth centuries, historians have on the whole, in deciding what constitutes historical evidence, clung to the idea of the primacy of the written word, of textual sources, and have been satisfied to leave the business of dating and interpreting ancient artefacts and material remains of human civilisations to prehistorians and archaeologists. While it has to be granted that these boundaries have occasionally been breached in some areas, such as in ancient Roman or Greek histories or in art history, debates in the historical profession over issues raised by the evidence of memory, personal experience, and legends and myths, have once again highlighted the value of written sources. True, historians now acknowledge that history is only one way among many of telling the past, but the idea of the archive a repository of written sources is still central to how historians think of what constitutes the activity called research. We imagine prehistorians and archaeologists as people who go digging around, literally, in unfamiliar places to find their treasure-troves of evidence; when we speak of historians, we still think of a group of people prepared to suffer the consequences of prolonged exposure to the dust that usually collects over old documents. The French once used to say, no documents, no history; the moral rule among historians still seems to be: no sniffles and sneezes, no history! ..."--Foreword.